Systematic review Evaluasi Keamanan Penggunaan Obat Tradisional di Indonesia - Manno, Muhammad Reski; Anggraini, Diva Nur; Anasiru, Rayhan; Oetari, R.A (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Indonesia, as a country with abundant biodiversity, has long used traditional medicinal plants to treat various diseases. The use of traditional medicine by the Indonesian people has been going on for a long time and is diverse, although there are still shortcomings in research related to its efficacy and safety. This study aims to evaluate how the Indonesian people use traditional medicine, including dosage, frequency, processing methods, and applications, as well as to assess the safety and effectiveness of its use. The method used is a systematic review with PRISMA guidance, where a literature search was conducted in the PubMed database using keywords related to the use of traditional medicine in Indonesia. From the search results, ten relevant articles were obtained which were analyzed. The results of the study indicate that although the use of traditional medicine is quite good, further research is still needed regarding the right dosage, the right choice of ingredients, and safe use methods. In addition, the importance of education, supervision, and the role of pharmacists and related agencies in ensuring the safety and effectiveness of traditional medicine in the community is also emphasized. This study is expected to contribute to increasing the understanding of the Indonesian people regarding the safe and effective use of traditional medicine.